1991
DOI: 10.1038/sj.bdj.4807424
|View full text |Cite
|
Sign up to set email alerts
|

Updating practices among Yorkshire general dental practitioners

Abstract: Ninety-eight per cent was the response achieved by a June 1989 postal survey to determine how general dental practitioners (GDPs) in Yorkshire Region maintain their professional knowledge. Such a good response adds confidence to the survey's findings which show many GDPs are educationally active and use a variety of media to keep up to date. Nevertheless, there remains a substantial proportion who should be doing more and need encouragement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…Long et al 5 reporting on GDP course attendance in Yorkshire, noted that 9% had not attended a course in the preceding 5 years. Although this report did not break down the number of attendances, the figures quoted indicated that the majority of the respondents would not have satisfied the GDC's requirements.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Long et al 5 reporting on GDP course attendance in Yorkshire, noted that 9% had not attended a course in the preceding 5 years. Although this report did not break down the number of attendances, the figures quoted indicated that the majority of the respondents would not have satisfied the GDC's requirements.…”
mentioning
confidence: 99%
“…Long et al 5 reported that the vast majority of respondents in their study considered it essential that practitioners were reimbursed for costs of attendance at courses and any resultant loss of income. Several reports have suggested that loss of income is a disincentive to course attendance, 6,[8][9][10] Miller et al, 9 investigating factors relating to the variation in levels of motivation to learn among established medical practitioners, identified isolation, workload, and financial loss as major factors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although this question included all postgraduate education courses and not just Section 63, this appears to compare favourably with a study carried out among GDPs in Yorkshire. 6 Earlier studies in 1991 and 1993 also indicated a low uptake of Section 63 courses by GDPs both from a self-reporting questionnaire, 11 and from Family Health Service Authority (FHSA) data. 12 The results from this present study suggest an increased commitment to postgraduate education, however, it was impossible to validate the GDPs sessional attendance at postgraduate courses due to the anonymous nature of the survey.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there is evidence of considerable take-up of these opportunities (Mouatt et al; 2 Long et al; 3 Walmsley and Frame [4][5] ), a significant number of practising dentists do not attend short courses. For example, in a study of approximately one third of GDPs in Yorkshire (number=307), Mercer et al 6 found that 13% had not attended any courses and that non-attendance was increasing.…”
Section: Introductionmentioning
confidence: 99%